2021
DOI: 10.1111/adj.12864
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status of newly admitted residents living in residential aged care

Abstract: Background: It is important to understand whether older people are admitted into residential care with existing dental diseases or their oral health deteriorates while residing in residential care. There is, however, little research available exploring the oral health status of people newly admitted into residential care. Understanding this disease trend would lead to effective prevention and treatment strategies to be trialled and implemented prior to admission. In this crosssectional study, we hypothesize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The prevalence of untreated decay and/or gum diseases, associated with an unsatisfactory oral cleanliness of older people living in residential aged care facilities, is frequently reported in the literature. 6,12,[19][20][21][22][23][24] There is, however, little reported on what type of dental treatments people in residential care require. 10,11,22,25 The Reach-OHT service found that diagnosis of dental diseases and treatment planning with adjunct preventive therapy were the predominant combination of treatments required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of untreated decay and/or gum diseases, associated with an unsatisfactory oral cleanliness of older people living in residential aged care facilities, is frequently reported in the literature. 6,12,[19][20][21][22][23][24] There is, however, little reported on what type of dental treatments people in residential care require. 10,11,22,25 The Reach-OHT service found that diagnosis of dental diseases and treatment planning with adjunct preventive therapy were the predominant combination of treatments required.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of untreated decay and/or gum diseases, associated with an unsatisfactory oral cleanliness of older people living in residential aged care facilities, is frequently reported in the literature 6,12,19–24 . There is, however, little reported on what type of dental treatments people in residential care require 10,11,22,25 .…”
Section: Discussionmentioning
confidence: 99%
“…
Dental professionals globally are experiencing the effects of an increasing population of frail, and care-dependent patients who are retaining their teeth into older age. [1][2][3][4][5][6] As the restorative cycle tends to move dentition into more complex restorative management, the older patient is more likely to have prosthodontics that are also increasingly difficult to manage if they are frail and care-dependent. 7
…”
mentioning
confidence: 99%